A case of thalamic hemorrhage with takotsubo cardiomyopathy. Issue 3 (30th April 2014) - Inoue, Teruhiro; Yanagawa, Youichi; Omori, Kazuhiko; Osaka, Hiromichi; Oode, Yasumasa; Sugita, Manabu; Okamoto, Ken
<x xml:space="preserve">Abstract</x> Case A 76‐year‐old woman was found unconscious by her family. She had suffered a fall and was soaked in kerosene. On arrival at our emergency department, she was unconscious, normotensive, with right hemiplegia and chemical burns. A computed tomographic scan of her head indicated left thalamic hemorrhage. An electrocardiogram showed ST elevation at the precardial leads. An echocardiogram revealed characteristic of takotsubo cardiomyopathy. Outcome The patient was intubated and treated conservatively. She was transferred to another hospital for rehabilitation after complete epithelization of the chemical burn. This is the second reported case of thalamic hemorrhage with takotsubo cardiomyopathy. The thalamic hemorrhage might have induced autonomic disturbances and caused the takotsubo cardiomyopathy in this case. Conclusion Physicians should pay attention to the potential complication of takotsubo cardiomyopathy, which may affect cardiopulmonary function even when patients are being treated for intracerebral hemorrhage.